2009
DOI: 10.1007/s10578-009-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Sleep Arousal and Sleep Problems of Anxiety-Disordered Youth

Abstract: The current study examined sleep problems and pre-sleep arousal among 52 anxious children and adolescents, aged 7-14 years, in relation to age, sex, ethnicity, and primary anxiety disorder. Assessment included structured diagnostic interviews and parent and child completed measures of sleep problems and pre-sleep arousal. Overall, 85% of parents reported clinically-significant child sleep problems, whereas 54% of youth reported trouble sleeping. Young children, those with primary generalized anxiety disorder, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
129
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(150 citation statements)
references
References 39 publications
(49 reference statements)
15
129
3
1
Order By: Relevance
“…The methods used may contribute to the results observed: some studies have shown that a greater number of sleep problems are revealed using child-reported (as against parent-reported) data [13,14] . Interestingly, this pattern appears to be reversed in clinical samples, with parents reporting more problems than the children themselves [2,15] .…”
Section: Methodological Issuesmentioning
confidence: 98%
See 2 more Smart Citations
“…The methods used may contribute to the results observed: some studies have shown that a greater number of sleep problems are revealed using child-reported (as against parent-reported) data [13,14] . Interestingly, this pattern appears to be reversed in clinical samples, with parents reporting more problems than the children themselves [2,15] .…”
Section: Methodological Issuesmentioning
confidence: 98%
“…Some studies use single-item measures. For instance, the children and adolescents investigated by Alfano and colleagues [2] were asked if they have 'trouble sleeping' and/or 'trouble waking in the morning'; or a longitudinal French cohort study where parents were asked, 'Does your child have sleep problems?' [10] .…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychophysiological insomnia may be more evident in older children and adolescents given the advancement in cognitive abilities leading them to be concerned and worried about the impact of their sleep on daytime behaviour. Indeed there is a growing body of evidence that catastrophic worry, dysfunctional beliefs about sleep and cognitive pre--sleep arousal are characteristic of children, teenagers and young adults reported to experience sleep disturbances (Barclay and Gregory 2010;Gregory et al 2009b;Gregory et al 2010;Alfano et al 2010;Gregory et al 2008b;Alfano et al 2009 (Hublin et al 1998b).…”
Section: Behavioural Insomnia Of Childhood: Difficulties Associated Wmentioning
confidence: 99%
“…Further, sleep has reduced restorative value, because recovery sleep tends to occur at an inappropriate circadian phase (Carskadon, 2011). Adolescents are also vulnerable to the same processes that cause insomnia in adults, such as susceptibility to hyperarousal (Alfano, Pina, Zerr, & Villalta, 2010;Blake et al, 2017a;Riemann et al, 2010).…”
Section: Introductionmentioning
confidence: 99%